Effects of socioeconomic status & sex on attentiveness to physical attractiveness. - Colico, Christine; Obar, Marilene (2005)
This study tested the hypotheses that women are more attentive than men on their physical attractiveness and that individuals with high socioeconomic status are more attentive than low socioeconomic status individuals. To test these hypotheses, a survey was done on 180 (80 males and 100 female) students of St. Scholastica's College of Health Sciences. After the exclusion of respondents whose family size exceeded six and respondents with incomplete answers on the survey questionnaire, the mean of the monthly family income of remaining respondents were computed. Student's whose monthly family income exceeded the mean were categorized as high status students and those students with monthly family income below the mean were categorized as low status students. students with monthly family income equal with the mean income were taken out of the sample. After this process, the researchers end up with 100 subjects (50 males and 50 females). After getting the socioeconomic status of the respondents, the answers on the Importance of Physical Attractiveness Test were assessed and a two-way analysis of variance was done to test the researchers' hypotheses. The result showed that their sex has no significant effect on a person's attentiveness to physical attractiveness (F value= 5.795). On the other hand, the study also showed that a person's socioeconomic status has a significant effect on his/her attentiveness to physical attractiveness. Furthermore, it was also found out that there is a significant interaction between a person's sex and socioeconomic status.
Undergraduate thesis (BASS Psychology) -- University of the Philippines, Tacloban.